What matters the most to people? Evidence from the OECD Better Life Index users' responses - Balestra, Carlotta (OECD Publishing, 2018)
The OECD Better Life Index is an interactive composite index that aggregates average measures of country's well-being outcomes through weights defined by users. This paper studies these weights by analysing the responses given by close to 130 000 users since 2011 to date. The paper has three goals. First, to investigate the factors shaping users' preferences over a set of 11 well-being dimensions. Second, to provide insights into users' preferences for a large group of countries which differ in terms of culture and living conditions. Third, to test for the effects of users' satisfaction with respect to a given well-being dimension on the weight they attach to it, across different population groups. Various empirical models are used to identify responses' patterns and see whether they can be accounted for by respondents' characteristics and their perceived well-being.
Keywords: Economics